Analysis of Working Capital for Micro, Small, and Medium Enterprises (UMKM) Tiga Dara, Banawa District, Donggala Regency - Nasrulhak Akkas (Universitas Muhammadiyah Palu, 2023)
This study aims to determine the management of working capital in Micro, Small, and Medium Enterprises in Tiga Dara, Banawa District, Donggala Regency, and to find out the contribution of working capital management efficiency to operating profits in Tiga Dara Micro, Small, and Medium Enterprises District of Banawa, Donggala Regency. This research is quantitative research with a descriptive approach using secondary data in the form of financial reports for Micro, Small, and Medium Enterprises in Tiga Dara consisting of a profit and loss report and a balance sheet for January to June 2021. The data analysis technique in this study uses ratio analysis consisting of Level Ratio Working Capital Turnover (TPMK), Return on Working Capital ratio, Return On Assets ratio, Gross Profit Margin ratio, and WratNet Profile Margin. This study shows that the level of efficiency in managing working capital at Micro, Small, and Medium Enterprises in Tiga Dara, Banawa District, Donggala Regency, is assessed from the assessment of the ratio of the level of turnover of capital working (TPMK) and the ratio of return working capital for the production of Banana Chips period months January-June 2021, is within the assessment criteria which is good so that the management of working capital for micro, small and medium enterprises is considered to be efficient. The results of the profitability analysis of Micro, small and medium enterprises in Tiga Dara Sub-district Banawa Donggala Regency show that when viewed and assessed from the ratio of Return on assets, it is in the category of poor assessment, while x x when viewed and assessed from the ratio of gross profit margin and net profit margin are in the good rating category. This means that the profitability performance of micro, small, and Medium Enterprises in Tiga Dara, Banawa District, Donggala Regency is assessed as having an inefficient return on asset ratio. In contrast, the profitability performance of Micro, Small, and Medium Enterprises in Tiga Dara, Banawa District, Donggala, is assessed from the ginxmarx profit ratio as efficient. For this reason, efficiency is urgently needed in difficult times like today, namely the Covid 19 pandemic. Therefore, Micro, Small, and Medium Enterprises in Tiga Dara, Banawa District, Donggala Regency must maintain and improve their business efficiency by utilizing existing resources to the maximum extent possible for maximum profit.